Discovery of a pattern of formation of mushroom-shaped tumors: a new approach to the study of intraocular melanomas (Ukrainian Journal of Ophthalmology, 2026)
The main purpose and motivation for this study was the assumption that intraocular mushroom-like melanomas, the spherical part of which is located outside the choroid, may have a retinal nature.This work is a retrospective study based on a preliminary investigation of histomorphological material with subsequent qualitative analysis. The work proposes a theoretical approach to solving a scientific problem, when the answer to the question of the histogenesis (place of origin) of the tumor is given not by studying histological patterns, but by analyzing the theoretical model of mushroom-like tumor formation.The theoretical model allows us to understand that no uveal tumor can form a mushroom-like nodule. Based on this, we formulated a pattern of formation of intraocular mushroom-like tumors, according to which the initial growth of a mushroom-like intraocular neoplasm is always associated with the spherical part, and the uveal part is a secondary place of their growth. This pattern applies to mushroom-like tumors of any localization. The specificity of intraocular mushroom-shaped tumors is that the growth of their spherical part is impossible without penetration into the choroid. This feature distinguishes them from mushroom-shaped tumors of other localizations, and this is one of the main reasons why their histogenesis has been difficult to detect.It has been shown that the mushroom-shaped tumor cannot originate from the choroid. This would be contrary to the laws of physics, not to mention the biological constraints regarding the growth pattern of tumors. The theoretical model of the mushroom-shaped melanoma suggests that its origin is linked to the retinal pigment epithelium. So, we are faced with the need for a fundamental revision of the classification and nomenclature of intraocular melanomas, which should be the next step.
Keywords: intraocular melanoma; mushroom tumors; retinal pigment epithelium; discovery